Differences In Quality of Life of Nasopharyngeal Carcinoma Patients at Rsi Sultan Agung Semarang Observational Analytical Studies in Age, Gender, and Stage of Cancer - Fitrianisa, Nadya; Sulistyanto, Agung; Ayuningtyas, Putri Rokhima (International Journal of Human and Health Sciences (IJHHS), 2024)
Nasopharyngeal carcinoma is a malignant tumor in the head and neck area of squamous cell type located in the nasopharynx. Nasopharyngeal carcinoma in Indonesia is the 4th most malignant cancer and is considered one of the most malignant tumors with high mortality and morbidity. This study aims to determine the difference in quality of life in nasopharyngeal carcinoma patients with characteristics (age, gender, and stage of cancer) nasopharyngeal tumors. The research method was carried out with analytical observational through a cross sectional approach. The measuring instruments used in the form of EORTC QLQ-C30 and EORTC QLQ-H&N35 questionnaires were used to measure the quality of life of nasopharyngeal carcinoma patients at RSI Sultan Agung Semarang. The data were analyzed using a binary logistic regression test. The results of the study of nasopharyngeal carcinoma patients according to the characteristics at RSI Sultan Agung Semarang based on 13 respondents were dominated by male patients totaling 8 people (61.54%), aged 45 years as many as 8 people (61.54%), and cancer stages were divided into 6 people (≥46.15%) and 7 people (53.85%) in the early and advanced stages. The results of the Wald Test did not significantly differ in the quality of life of nasopharyngeal carcinoma patients at RSI Sultan Agung Semarang with each sig intention. The independent variables were age (p = 0.187), gender (p = 0.227), and cancer stage (p = 0.558). The independent variable that most affected the level of quality of life of nasopharyngeal carcinoma patients was gender with a value of Exp(B) = 5.394. The conclusion of this study is that there is no difference in quality of life in nasopharyngeal carcinoma patients with characteristics (age, gender, and stage of cancer) nasopharyngeal tumors. International Journal of Human and Health Sciences Vol. 08 No. 02 Apr’24 Page: 151-156